2012
DOI: 10.1080/03004430.2011.623779
|View full text |Cite
|
Sign up to set email alerts
|

Pre-school children's aggressive and pro-social behaviours in stressful situations

Abstract: The aim of our research was to investigate social and emotional skills that determine pre-schoolers' aggressive and pro-social behaviours in stressful situations. The sample of the empirical study consisted of 119 (36-48, 49-60 and 61-72 months) Hungarian children from six pre-schools. Instruments that were used: Coping strategy self-report and teacher-report questionnaires as well as hypothetical social situations interviews with puppets. The statistical analysis of pre-school teachers' questionnaires showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…Prosocial and aggressive behaviour may reflect normative ways of dealing with peer conflict. In conflict situations, including being teased by a peer or social exclusion, children aged 4–6 years engaged in more aggressive (e.g., hitting) and prosocial (e.g., negotiation) strategies than 3‐year‐old children (Zsolnai, Lesznyák, & Kasik, ). Furthermore, prosocial behaviour has been found to moderate the relationship between other cognitive abilities (theory of mind) at 5 years of age and relational aggression at 6 years of age (Renouf et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Prosocial and aggressive behaviour may reflect normative ways of dealing with peer conflict. In conflict situations, including being teased by a peer or social exclusion, children aged 4–6 years engaged in more aggressive (e.g., hitting) and prosocial (e.g., negotiation) strategies than 3‐year‐old children (Zsolnai, Lesznyák, & Kasik, ). Furthermore, prosocial behaviour has been found to moderate the relationship between other cognitive abilities (theory of mind) at 5 years of age and relational aggression at 6 years of age (Renouf et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In one preschool study, Chen and colleagues [28] found few gender differences on behavioral inhibition in Chinese and Canadian toddlers, suggesting that socialization in early childhood might play an essential role in gender differences in social-emotional disabilities that surface in later childhood. Furthermore, international studies addressing gender differences in young children's social-emotional competence have focused most often on a single cultural group or region [29][30][31][32][33][34], rather than comparisons across cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Hungarian studies found a significant correlation between social behavior and parents' level of education in preschool children and junior grade students, 1 and the correlation was found to be the strongest for mothers' education (e.g., Józsa, 2004;Zsolnai & Józsa, 2003;Zsolnai et al, 2012). These results suggest that educational attainment is a major factor in parenting style, which in turn has an effect on children's social behavior.…”
Section: Social Backgroundmentioning
confidence: 92%
“…Our previous studies of social competence used exclusively paper-based measurement tools (e.g., Kasik & Tóth, 2011;Zsolnai, Lesznyák, & Kasik, 2012), but now for the first time our data were collected online.…”
Section: The Present Studymentioning
confidence: 99%